S100A4 amplifies TGF-β-induced fibroblast activation in systemic sclerosis. Issue 9 (7th April 2014) - Tomcik, Michal; Palumbo-Zerr, Katrin; Zerr, Pawel; Avouac, Jerome; Dees, Clara; Sumova, Barbora; Distler, Alfiya; Beyer, Christian; Cerezo, Lucie Andres; Becvar, Radim; Distler, Oliver; Grigorian, Mariam; et al.
Abstract : Objectives: S100A4 is a calcium binding protein with regulatory functions in cell homeostasis, proliferation and differentiation that has been shown to promote cancer progression and metastasis. In the present study, we evaluated the role of S100A4 in fibroblast activation in systemic sclerosis (SSc). Methods: The expression of S100A4 was analysed in human samples, murine models of SSc and in cultured fibroblasts by real-time PCR, immunohistochemistry and western blot. The functional role of S100A4 was evaluated using siRNA, overexpression, recombinant protein and S100A4 knockout (S100A4 −/− ) mice. Transforming growth factor β (TGF-β) signalling was assessed by reporter assays, staining for phosphorylated Smad2/3 and analyses of target genes. Results: The expression of S100A4 was increased in SSc skin and in experimental fibrosis in a TGF-β/Smad-dependent manner. Overexpression of S100A4 or stimulation with recombinant S100A4 induced an activated phenotype in resting normal fibroblasts. In contrast, knockdown of S100A4 reduced the pro-fibrotic effects of TGF-β and decreased the release of collagen. S100A4 −/− mice were protected from bleomycin-induced skin fibrosis with reduced dermal thickening, decreased hydroxyproline content and lower myofibroblast counts. Deficiency of S100A4 also ameliorated fibrosis in the tight-skin-1 (Tsk-1) mouse model. Conclusions: We characterised S100A4 as a downstream mediator of the stimulatory effects of TGF-β on fibroblasts in SSc. TGF-β induces the expression of S100A4 to stimulate the release of collagen in SSc fibroblasts and induce fibrosis. Since S100A4 is essentially required for the pro-fibrotic effects of TGF-β and neutralising antibodies against S100A4 are currently evaluated, S100A4 might be a candidate for novel antifibrotic therapies.